Wavelet Galerkin Methods for Aerosol Dynamic Equations in Atmospheric Environment (Communications in Computational Physics, 2009)
Aerosol modelling is very important to study and simulate the behavior ofaerosol dynamics in atmospheric environment. In this paper, we consider the generalnonlinear aerosol dynamic equations which describe the evolution of the aerosoldistribution. Continuous time and discrete time wavelet Galerkin methods are proposedfor solving this problem. By using the Schauder's fixed point theorem and thevariational technique, the global existence and uniqueness of solution of continuoustime wavelet numerical methods are established for the nonlinear aerosol dynamicswith sufficiently smooth initial conditions. Optimal error estimates are obtained forboth continuous and discrete time wavelet Galerkin schemes. Numerical examples aregiven to show the efficiency of the wavelet technique